ANALISIS PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI, PENGENDALIAN INTERNAL, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN INTEGRITAS KARYAWAN SEBAGAI VARIABEL INTERVENING - Silvia Sari; Rini Septiowati (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The success of an organization is strongly influenced by employee performance. Every company always improves employee performance to achieve the goals it wants. This study aims to determine the effect of applying accounting information systems, internal control, work motivation and organizational culture on employee performance with employee integrity as an intervening variable. The method used in this study is a quantitative approach and uses a purposive sampling method. The data in this study are primary data obtained from distributing questionnaires directly to accounting students in the Pamulang University employee class, especially students in the accounting study program. The number of samples used is 100 respondents. Data were analyzed by Structural Equation Modeling (SEM). Exogenous latent variables are the application of accounting information systems, internal control, work motivation and organizational culture. While employee performance as an endogenous latent variable with employee integrity as an intervening variable. The results showed that internal control variables formed employee integrity variables (loading factor = 0.69) and employee integrity variables were proven to influence employee performance variables (loading factor = 0.97). This provides an overview in the form of recommendations for improving internal control from the employee side which will have an impact on improving organizational performance.